Many but small HIV-1 non-B transmission chains in the Netherlands. (1st January 2022) - Bezemer, Daniela; Blenkinsop, Alexandra; Hall, Matthew; van Sighem, Ard; Cornelissen, Marion; Wessels, Els; van Kampen, Jeroen; van de Laar, Thijs; Reiss, Peter; Fraser, Christophe; Ratmann, Oliver
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: The aim of this study was to investigate introductions and spread of different HIV-1 subtypes in the Netherlands. Design: We identified distinct HIV-1 transmission chains in the Netherlands within the global epidemic context through viral phylogenetic analysis of partial HIV-1 polymerase sequences from individuals enrolled in the ATHENA national HIV cohort of all persons in care since 1996, and publicly available international background sequences. Methods: Viral lineages circulating in the Netherlands were identified through maximum parsimony phylogeographic analysis. The proportion of HIV-1 infections acquired in-country among heterosexuals and MSM was estimated from phylogenetically observed, national transmission chains using a branching process model that accounts for incomplete sampling. Results: As of 1 January 2019, 2589 (24%) of 10 971 (41%) HIV-1 sequenced individuals in ATHENA had non-B subtypes (A1, C, D, F, G) or circulating recombinant forms (CRF01AE, CRF02AG, CRF06-cpx). The 1588 heterosexuals were in 1224, and 536 MSM in 270 phylogenetically observed transmission chains. After adjustments for incomplete sampling, most heterosexual (75%) and MSM (76%) transmission chains were estimated to include only the individual introducing the virus (size = 1). Onward transmission occurred mostly in chains size 2–5 amongst heterosexuals (62%) and in chains size at least 10 amongst MSM (64%). Considering some chains originated in-country from other risk-groups, 40% (95% confidence interval: 36–44) of non-B-infected heterosexuals and 62% (95% confidence interval: 49–73) of MSM-acquired infection in-country. Conclusion: Although most HIV-1 non-B introductions showed no or very little onward transmission, a considerable proportion of non-B infections amongst both heterosexuals and MSM in the Netherlands have been acquired in-country.